2018
DOI: 10.1177/1029864918782581
|View full text |Cite
|
Sign up to set email alerts
|

Does music help children grow up? Parental views from a longitudinal panel study

Abstract: Previous research has identified families as hubs for musical development, but little is known about the reciprocal effects on familial dynamics. Here, we address the long-term associations between familial music and parental perceptions of their children’s personality. To these ends, we analysed a subset of data from the German Panel Analysis of Intimate Relationships and Family Dynamics study, a longitudinal cohort study. A total of 839 data sets from parents with their children, covering four waves over a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…Thus, it is possible that these cultural tendencies may be embedded in Brazilian's beliefs and practices concerning music parenting/caregiving (Ilari et al, 2011 ). Alternatively, it may be that caregivers found in these shared musical experiences an opportunity for safe time-passing (Schubert, 2009 ; Schäfer et al, 2013 ), entertainment (Trehub and Schellenberg, 1995 ), caregiver-child bonding (Creighton et al, 2013 ; Boer and Abubakar, 2014 ; Persico et al, 2017 ; Fancourt and Perkins, 2018a , b ), or to promote individual and collective well-being (Saarikallio, 2009 ; Schäfer et al, 2013 ; Kreutz and Feldhaus, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is possible that these cultural tendencies may be embedded in Brazilian's beliefs and practices concerning music parenting/caregiving (Ilari et al, 2011 ). Alternatively, it may be that caregivers found in these shared musical experiences an opportunity for safe time-passing (Schubert, 2009 ; Schäfer et al, 2013 ), entertainment (Trehub and Schellenberg, 1995 ), caregiver-child bonding (Creighton et al, 2013 ; Boer and Abubakar, 2014 ; Persico et al, 2017 ; Fancourt and Perkins, 2018a , b ), or to promote individual and collective well-being (Saarikallio, 2009 ; Schäfer et al, 2013 ; Kreutz and Feldhaus, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Musical parenting plays a central role in childhood musical experiences. A robust body of literature demonstrates that caregivers of children under the age of 6 years tend to interact musically with their children (Custodero and Johnson-Green, 2003 ; Young, 2003 ; Ilari, 2005 ; Addessi, 2009 ; Barrett, 2009 ; de Vries, 2009 ; Mehr, 2014 ; Pitt and Hargreaves, 2017 ), although the frequency of joint musical interactions seems to progressively diminish as the child reaches toddlerhood (Custodero et al, 2003 ; Kreutz and Feldhaus, 2020 ). Caregiver-child musical activities in the preschool years involve, for instance, joint and supported singing, improvising songs to accompany everyday routines, playing musical toys and instruments with the child, dancing, and listening to recorded music (Custodero and Johnson-Green, 2003 ; Addessi, 2009 ; Barrett, 2009 ; Trehub et al, 2015 ; Corbeil et al, 2016 ; Politimou et al, 2018 ; Cirelli et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…appreciation). Overall, the study showed that music activities in the family setting have an effect on family dynamics, relationships and children's personality [20], emphasizing that musical engagement at home is an important factor to consider when conducting studies with children.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Kreutz and Feldhaus [20] examined the development of familial musical engagement as well as other everyday activities, such as reading and shopping and how these are related to children's personality. They revealed that the amount of musical activity declined in this age range as children grew older (ages ranged from seven to 14 years), in contrast to other activities which tended to remain stable over time.…”
Section: Introductionmentioning
confidence: 99%